Commando" units, the fourth historical state, from 1956-1960 - Elite National Liberation Army - khiter, aziz (The Algerian Historical Journal, 2026)
This article seeks to uncover a military organization that was created within the units of the Liberation Army in the fourth historical state to make this state distinct from the rest of the other states in terms of organization and structure. It also sheds light on the personality that was behind the creation of this organization, and the great role it played against Enemy units and aides. One of the most important results that we concluded in this research is that the commando units for which this state was famous had a bountiful share of military heroics and achievements, so that they were truly representative of the "elite" of the liberation army in this state.